'Record of my journeyings in the Coral Sea': Randolph Bedford's 1906 album of the Solomon Islands. Issue 1 (1st May 2020) - Quanchi, Max
Albums and scrapbooks are rarely the focus of research. This article examines the motivation and context for a unique and rare album compiled by a 'special correspondent' ‐ George Randolph Bedford, an aspiring Federal politician, journalist and writer ‐ who visited the Solomon Islands in 1906 on a personal fact-finding mission. His scrapbook contains 212 photographs and a series of articles on the Solomon Islands that he had published in illustrated weekend newspapers in Australia in 1906 and early 1907. The Australian colonies had just federated, Britain had just passed control of Papua to Australia and, in the New Hebrides, Britain and France were about to announce a condominium had been formed. Tonga, Niue and the Cook Islands were also the subject of imperial manoeuvring. In Queensland, Kanakas were being sent home as the labour trade was abolished. The scrapbook is therefore a window on to imperial diplomacy, colonial expansion and Australian visions of a relationship with the Pacific, the boom in illustrated newspapers, early photography and personal ambition to become an expert on the islands.